IMPLEMENTATION OF THE HEALTH PROTOCOL CONCERNING COVID-19 PREVENTION TO SELLERS - Rupang Rampo La'bi'; Ribka Limbu; Helga J. N. Ndun (Journal of Health and Behavioral Science, 2022)
COVID-19 is an infectious disease caused by SARS-CoV-2. The health protocol is set as an effort to prevent and control the spread of COVID-19. This study aims to describe the application of health protocols related to the prevention of COVID-19 on sellers at the Kasih market in Kupang City. This type of research is descriptive with a qualitative approach. There were 8 informants in this study and the sampling selection using purposive sampling. The analysis was conducted qualitatively based on unstructured interviews. The results showed that the informants had good knowledge because they knew about the meaning, transmission, and prevention of COVID-19, as well as knowing the application of health protocols. Informants also had a positive attitude towards COVID-19 and the attitude of using masks and washing hands but had a negative attitude towards the application of social distancing. The PHBS facilities at the Kasih market in Kupang City are adequate.